2019
DOI: 10.1002/cbin.11120
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized low‐density lipoprotein promotes vascular endothelial cell dysfunction by stimulating miR‐496 expression and inhibiting the Hippo pathway effector YAP

Abstract: Oxidized low‐density lipoprotein (ox‐LDL) can damage vascular endothelial cells and cause atherosclerosis, but its epigenetic regulatory mechanism has not been fully elucidated. We show that ox‐LDL induced significant apoptosis and loss of function in human umbilical vascular endothelial cells (HUVECs). At the same time, ox‐LDL significantly decreased the expression of Hippo–YAP/ZAP (Yes‐associated protein/YLP motif–containing 1) pathway proteins as compared to that of the control. The luciferase reporter syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 32 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Notably, phosphorylated YAP (p-YAP) cannot enter the nucleus, and remains in the cytoplasm where it cannot regulate transcription (13). Furthermore, it has been demonstrated that YAP serves an important role in the mediation of the proliferation, migration, apoptosis and phenotypic transition of ECs (14) and vascular smooth muscle cells (15). Additionally, a previous study found that the Hippo-YAP signaling pathway is regulated by Ang II signaling, and that its reactivation induces apoptosis and proliferation in podocytes (16).…”
Section: Introductionmentioning
confidence: 98%
“…Notably, phosphorylated YAP (p-YAP) cannot enter the nucleus, and remains in the cytoplasm where it cannot regulate transcription (13). Furthermore, it has been demonstrated that YAP serves an important role in the mediation of the proliferation, migration, apoptosis and phenotypic transition of ECs (14) and vascular smooth muscle cells (15). Additionally, a previous study found that the Hippo-YAP signaling pathway is regulated by Ang II signaling, and that its reactivation induces apoptosis and proliferation in podocytes (16).…”
Section: Introductionmentioning
confidence: 98%
“…miR-496 has been identified to participate in various pathobiological processes (15,16). However, the functions of miR-496 in OS have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 HLD is known to cause endothelial dysfunction as a result of an elevated oxidized LDL-C (ox-LDL) level. Ox-LDL can damage vascular endothelium by 1) downregulating Hippo Yes-associated protein/YLP motif contain 1 (Hippo-YAP/ZAP) pathway which in turn interferes with cardiovascular remodeling, 31 2) by inducing the apoptosis of vascular endothelial as a result of upregulated expression of autophagy-related protein, 32 and 3) by inhibiting vascular relaxations induced by nitric oxide. 33 In theory, HLD patients are more likely to have endothelial dysfunction, which may facilitate the pathophysiologic basis for the occurrence of TCM.…”
Section: Discussionmentioning
confidence: 99%